Konsep Manajemen Berdasarkan Surat Al-Ashri dan Hadits yang Relevan (Manajemen Waktu) - Oktawira, Leni; Bustamam, Risman; Apriyenti, Apriyenti (Indo-MathEdu Intellectuals Journal, 2025)
This research is motivated by the importance of the value of time in the Qur'an, especially as reflected in Surah Al-Ashr. This surah provides strong cues regarding the principles that can be used as a foundation in the implementation of Islamic Education Management. Among these principles are the importance of discipline, efficient, effective, and productive use of time, and professionalism based on faith. Responsibility in work is not only addressed to superiors, but also to Allah SWT. Leaders of educational institutions are required to provide guidance, direction and supervision, as well as being a role model through perseverance and patience. This type of research is library research that focuses on literature review and relevant written sources. The results showed that Surah Al-Ashr can be interpreted in the perspective of Islamic Education Management science through four managerial functions, namely: (1) Planning, which is reflected in the word wal-'ashr (by time); (2) Controlling, through the word khusr (loss); (3) Actuating, which is reflected in aamanuu wa 'amilush-shaalihaat (believing and doing good deeds); and (4) Motivating and encouraging, through the phrase watawaashou bil-haqqi watawaashou bish-shabr (advise one another in truth and patience).